The Concept of Evil in 4 Maccabees - Moscicke, Hans (The journal of Jewish thought & philosophy, 2017)
The concept of evil in 4 Maccabees differs from what we find in most ancient Jewish literature, and little attention has been paid to its philosophical background. In this article I submit that the author of 4 Maccabees has absorbed and adapted a Stoic conception of evil into his Jewish philosophy. I trace the concept of evil in Stoicism and in 4 Maccabees using the categories of value theory, natural law, and the emotions. The outcome is an integrative philosophy that embraces vice as the sole evil, yet maintains a belief in the “goodness” of an afterlife; redefines natural law in terms of the Torah, reckoning any deviance from that Law as vicious; and conceives of the emotions as false belief and the cause of evil behavior, while still maintaining their God-given nature.